Pencegahan Anemia Pada Remaja Putri, Mahasiswa FKM Universitas Cendrawasih - Katarina Lodia Tuturop; Konstantina Martina Pariaribo; Asriati Asriati; Natalia Paskawati Adimuntja; Muhammad Akbar Nurdin (Universitas Negeri Makassar, 2023)
Anemia is a problem health global society that occurs in developing countries as well as developed countries. The effect of anemia on everything age have consequence big for health man as well as burden social economy. The impact of anemia on adolescents is existence lateness growth physical, disorder behavior as well as emotional that can affect the process of growth and development cell lowering brain _ power stand body, easy weak and hungry, concentration study disturbed, and lack of productivity. Anemia that occurs with age teenager could continue until age adults who can contribute high maternal and infant mortality rates _ premature birth, and LBW. Remember the impact that can caused if somebody have anemia, it is very important to do effort prevention of anemia. Efforts that can conducted is through screening for anemia inadolescents princess and education about prevention of anemia. This activity was held in the Hall of the Faculty of Public Health Uncen on Wednesday, September 28, 2022 with participants teenager Princess aged 15-24 years. The results of this screening activity are: most participants _ 20 years old that is as much as 49.50%, and the incidence of anemia was found in the mild category as much as 7.93% and most do not suffer from anemia (92.07%).